Pharmacokinetics and bioequivalence of two cyclosporine oral solution formulations in cats - Yang, Yuxin; Kong, Jingyuan; Liu, Yu; Wu, Qinyao; Cao, Yuying; Qiu, Jicheng; Zhang, Lu; Gong, Xiaohui; Zhao, Fuhua; Cao, Xingyuan; Wang, Jianzhong (Frontiers in Veterinary Science, 2022)
The pharmacokinetic profiles and bioequivalence of two cyclosporine oral solutions were investigated in cats. Twenty-four cats were randomly allocated to two equally sized treatment groups in a randomized four-cycle, and dual-sequence cross-over design. Test and reference articles were orally administered in a single dose of 7 mg/kg Bodyweight. Serial blood samples were collected, and blood cyclosporine concentration was determined by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS/MS). No significant differences were present in the major pharmacokinetic parameters (Cmax, AUC0−last,) between the two formulations. The blood profiles of cyclosporine following the administration of both formulations were similar. The findings of the study suggested that the two articles were bioequivalent for cyclosporine oral solution.